Characterization of Solid Concrete Block Masonry - MUKESH KUMAR (Mehran University Research Journal of Engineering and Technology, 2017)
Masonry walls constituted of solid concrete blocks are used very commonly in the framed structures as well as in the load bearing structures in various parts of Pakistan. However, very limited understanding on the characteristics and behavior of this type of masonry walls, particularly from the perspective of the seismic design and assessment, is available. This paper attempts to investigate the important characteristics, such as strength and stiffness, of the walls constructed from two grades/types of these blocks, referred as Type-1 and Type-2 blocks. The dimensions of Type-1 and Type-2 blocks are 300x200x150mm and 300x200x100mm, respectively. Compressive strength, bond strength, coefficient of friction, and diagonal (shear)strength of the masonry blocks and its assemblages are obtained from detailed experimental work. In the due course, the influence of the presence of the plaster on the masonry prisms made of two and three blocks subjected to compression and shear force respectively are investigated. The outcomes of the experimental investigation presented herein can be used effectively in macro and micro modelling of infill in framed structures as well as load bearing structures.